Effect of sowing dates, crop geometry and host range on powdery mildew (Erysiphe polygoni) of fenugreek, Trigonella foenum graecum L. - Kumawat, R Kumawat*, K S Shekhawat & K (Journal of Spices and Aromatic Crops, 2017)
In Rajasthan, fenugreek crop is attacked by a number of diseases. Powdery mildew of fenugreek is an important and serious disease caused by Erysiphe polygoni. Date of sowing and crop geometry greatly influenced the disease intensity of powdery mildew on fenugreek during the two consecutive years 2012-13 and 2013-14. Early sown crop exhibited more disease development as compared to late sown crop. November 30th sown crop recorded minimum per cent disease intensity, whereas 10th October sown crop recorded maximum per cent disease intensity and minimum seed yield. The crop was sown on 30th October registered maximum seed yield (16.48 q/ha) with 61.10 per cent disease intensity. The wider spacing of 15 x 45 cm, 15 x 30 cm and 10 x 45 cm between rows and within rows recorded minimum per cent disease intensity (36.11, 39.66 and 45.39) respectively. However, closer spacing 5 x 15 cm recorded maximum seed yield and per cent disease intensity. Out of fifteen host species powdery mildew symptoms were observed on Pisum sativum, Cuminum cyminum, Coriandrum sativum, Calendula officinalis, Lathyrus odoratus and Foeniculum vulgur under caged conditions.